Development and validation of UV-spectrophotometric methods for quantitative estimation of Prothionamide in pure and pharmaceutical dosage forms - Debnath, Sujit Kumar; Saisivam, S.; Dash, Dillip Kumar; Debnath, Monalisha (International Current Pharmaceutical Journal, 2015)
UV Spectrophotometric method was developed and validated for the quantitative determination of Prothionamide in bulk drug and in pharmaceutical formulations. Prothionamide shows the maximum absorbance at 288 nm in phosphate buffer (pH 7.4). Prothionamide follows Beers law in the concentration range of 4-20 µg/ml (r2 = 0.999). The detection limit (DL) and quantitation limit (QL) were 0.406 and 1.229 µg/ml respectively. Accuracy and precision were found to be satisfactory. The developed methods were validated according to ICH guidelines. All the validation parameters were found to be satisfactory accordance with the standard values. Therefore, the proposed method can be used for routine practice for the determination of Prothionamide in assay of bulk drug and pharmaceutical formulations. International Current Pharmaceutical Journal, June 2015, 4(7): 402-404